METHOD OF ASSESSMENT OF RADIOTHERAPEUTIC INTERVAL IN RADIATION THERAPY FOR CANCER CONSIDERING DOSE FRACTIONATION REGIMEN - V. A. Lisin (Сибирский онкологический журнал, 2016)
The analysis of currently available definitions of the term «radiotherapeutic interval» (RTI) has showed that they contain significant uncertainties and do not take into account the dose fractionation regimen. The aim of the study was to analyze the current approaches to the definition of the term «radiotherapeutic interval» and to propose a new definition excluding uncertainties and taking into account the dose fractionation regi- men. materials and methods. A new approach to the assessment of radiotherapeutic interval was applied to superficial tumors treated with X-rays and fast electron beams. The features of dose distributions characteristic of X-ray and monoenergetic fast electron beams generated in radiotherapy of superficial malignant tumors 10 SIBERIAN JOURNAL OF ONCOLOGY. 2016. VOL. 15, № 3. Р. 5-11 в.а. лисин сПОсОб ОЦенКИ раДИОтераПевтИчесКОГО Интервала were studied. The relationship between radiotherapeutic interval and tumor size for Х-ray and monoenergetic fast electron beam radiotherapy was calculated. The algorithm of calculation was consistent with the new definition of the concept of «radiotherapeutic interval». Results. A new approach to the definition of «radio- therapeutic interval», which avoids the previous definition’s inherent uncertainties and contradictions and takes into account the dose fractionation regimen, has been proposed.